Ecological Analysis of Crime Rates and Police Discretion with Young Persons: A Replication - Schulenberg, Jennifer L. (Canadian journal of criminology and criminal justice, 2007)
This research note replicates previous research published in the Journal ( [ABSTRACT FROM AUTHOR]